Interim results of the Ph-negative acute lymphoblastic leukemia treatment in adult patients (results of Russian research group of ALL treatment (RALL)) - E. N. Parovichnikova; V. V. Troitskaya; A. N. Sokolov; Z. Kh. Akhmerzaeva; L. A. Kuzmina; L. P. Mendeleeva; G. A. Klyasova; S. K. Kravchenko; Ye. O. Gribanova; S. N. Bondarenko; O. Yu. Baranova; T. S. Kaporskaya; et al. (Онкогематология)
An interim analysis of long-term treatment results for 202 patients with acute lymphoblastic leukemia (ALL), aged 15–60 years, received therapy according protocol ALL-2009 was shown. The basic principle of ALL-2009 was non-aggressive, but continued cytostatic exposure, as well as the reproducibility in a regional hematology centers. Long-term treatment results of ALL-2009 are 2 times higher than the previously obtained in adult ALL patients within the Russian clinical multicenter studies of adult ALL. The 5‑year overall survival of patients younger than 30 years was 73.6 %, relapse-free survival (RFS) – 71.5 %, compared with 52.7 % and 61.8 % in patients aged 30 years and older, respectively. In patients with B-precursor ALL with normal karyotype of blast cells significantly higher 5‑year RFS (82.1 %) compared to patients with abnormal karyotype (58.8 %) was registered. For T-ALL cytogenetic characteristics of blast cells had no prognostic significance. For patients with T-ALL important to perform autologous stem cell transplantation as a later consolidation, as this significantly reducerelapse rate (from 33 to 0 %).